Successful treatment of testicular pain with peripheral nerve stimulation of the cutaneous branch of the ilioinguinal and genital branch of the genitofemoral nerves. - Rosendal, F; Moir, L; de Pennington, N; Green, A; Aziz, T (2013)
OBJECTIVES: To assess the effect of peripheral nerve stimulation on neuropathic testicular pain. MATERIAL AND METHODS: A 30-year-old man with a four-year history of chronic testicular pain following scrotal hydrocele surgery had two percutaneous leads implanted in his groin and low-frequency stimulation of the cutaneous branch of the ilioinguinal and genital branch of the genitofemoral nerves. RESULT: At seven-month follow-up, the pain intensity had declined from 9/10 to 2/10 on the numeric rating scale. CONCLUSION: We report the successful implantation of an ilioinguinal and genitofemoral nerve stimulator for sustained suppression of intractable neuropathic testicular pain.